MiR-223-3p Alleviates Vascular Endothelial Injury by Targeting IL6ST in Kawasaki Disease - Wang, Xiang; Ding, Yue yue; Chen, Ye; Xu, Qiu qin; Qian, Guang hui; Qian, Wei guo; Cao, Lei; Zhou, Wan ping; Hou, Miao; Lv, Hai tao (Frontiers in Pediatrics, 2019)
Kawasaki disease (KD) is an acute, self-limiting systemic vascular inflammatory disorder.It causes pathological changes majorly in small and medium-sized arteries, especially the coronary arteries, which increases the risk of developing coronary heart disease as adults. miR-223-3p plays important roles in many diseases. However, less research was focused on the relationship between miR-223-3p and KD. In this study, we found that the expression of miR-223 was significantly high in serum from patients with Kawasaki disease (KD) and KD serum could increase miR-223 transcription levels in human coronary artery endothelial cells(HCAECs). MiR-223 could alleviate vascular endothelial damage in KD mice, and IL-6, E-selectin and ICAM-1 were negative in the sametime. Luciferase report assay showed that IL6ST is a target gene of miR-223. Overexpression of miR-223 downregulated IL6ST expression, and decreased the expression of p-STAT3 and NF-κB, while miR-223 inhibitor could reverse the above process. Taken together, the results suggest that miR-223 has an essential protective role in KD vascular endothelial injury by targeting IL6ST, and the miR-223 may be used as a potential biomarker for diagnosis of KD.